2021
DOI: 10.3390/ijerph18105294
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status of 12-Year-Old Hani Children in the Yunnan Province of China: A Cross-Sectional Study

Abstract: Background: The aim of this cross-sectional study was to investigate the oral health status of Hani 12-year-old children in Yunnan, a province in Southwest China. Method: This study employed a multistage sampling method to recruit children from local primary schools. Two calibrated dentists examined the status of dental caries, gingival bleeding and dental fluorosis by adopting the diagnosis criteria recommended by the World Health Organization. A self-administrated questionnaire was distributed. The chi-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This may also be related to girls’ preference for cariogenic foods. Univariate analysis in the present study and other studies have shown that the prevalence of caries experience was higher among individuals who frequently consumed sweet food items [ 19 – 21 ]. The prevalence of caries experience in rural district was found to be significantly higher compared to urban district.…”
Section: Discussionsupporting
confidence: 70%
“…This may also be related to girls’ preference for cariogenic foods. Univariate analysis in the present study and other studies have shown that the prevalence of caries experience was higher among individuals who frequently consumed sweet food items [ 19 – 21 ]. The prevalence of caries experience in rural district was found to be significantly higher compared to urban district.…”
Section: Discussionsupporting
confidence: 70%
“…According to the results of an oral epidemiological survey, prevalence varies greatly from region to region [8,[12][13][14][15]. The prevalence of gingivitis in children aged 12 years was 46.63% in the southern Chinese province of Sichuan [8] and 29.1% in the central province of Shandong [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of gingivitis in children aged 12 years was 46.63% in the southern Chinese province of Sichuan [8] and 29.1% in the central province of Shandong [12]. The prevalence also varies by ethnic group, with 93%, 61%, and 88% prevalence reported among the Dai, Hani, and Lisu ethnic groups in Yunnan Province, China, respectively [13][14][15]. No data are available for Jinzhou, which is a transportation hub in the north with a complex population comprising multiple ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…11 The prevalence also varies by ethnic group, with 93%, 61%, and 88% prevalence reported among the Dai, Hani, and Lisu ethnic groups in Yunnan Province, China, respectively. [12][13][14] No data are available for Jinzhou, which is a transportation hub in the north with a complex population comprising multiple ethnic groups. Therefore, the aim of this study was to investigate (1) the prevalence of gingivitis in children aged 6-12 years in Jinzhou, China, (2) the risk factors affecting the occurrence of gingivitis, and (3) the factors associated with the aggravation of gingivitis and also to use these ndings as a reference for improving the direction of oral catharsis.…”
Section: Introductionmentioning
confidence: 99%